Lean and digitalisation application in a micro-enterprise educational institution - John O’Shanahan; José Carlos Sá; M. Thenarasu; Manjeet Kharub; Olivia McDermott (Journal of Open Innovation: Technology, Market and Complexity)
This study aims to utilise Lean and basic digitalisation methods in a family-run Irish microenterprise and educational institution to improve customer service and reduce non-value added activities. This case study within an Irish educational provider and micro-enterprise utilised the structured Define, Measure, Analyse, Improve, and Control methodology to highlight areas of the educational institution's processes and services to improve. The project led to the use of Lean and basic digitalisation methods to identify non-value add activities in online exam delivery, attendance tracking, tutor contract setup and course scheduling, which resulted in reducing or eliminating over-processing and some automation of processes. The study, while only conducted in one educational institution and micro-enterprise, is an example of Lean implementation in an Irish second-level educational provider, and the learnings can be leveraged. The wider educational sector can benchmark how the improvement aided not only course delivery and scheduling but also attendance checking and payment scheduling. Educational organisations and micro enterprises can use this study to understand the benefits of adopting Lean, particularly in administration processes, to improve process efficiency and reduce non-value added activity. This is the first practical case study on Lean and digitisation deployment in an Irish second-level educational service provider, if not the first globally and one of few studies on Lean application in micro-enterprises. The study can be used to benchmark how Lean and digitisation can benefit microenterprises in particular and showcase innovation via the aforementioned areas.